Effects of repeated social defeat on adolescent mice on cocaine‐induced CPP and self‐administration in adulthood: integrity of the blood–brain barrier. (16th September 2015) - Rodríguez‐Arias, Marta; Montagud‐Romero, Sandra; Rubio‐Araiz, Ana; Aguilar, María A.; Martín‐García, Elena; Cabrera, Roberto; Maldonado, Rafael; Porcu, Francesca; Colado, María Isabel; Miñarro, José
Abstract: Social stress in adulthood enhances cocaine self‐administration, an effect that has been related with an increase in extracellular signal‐regulated kinase and p38α mitogen‐activated protein kinase phosphorylation. A detrimental effect of cocaine on blood–brain barrier (BBB) integrity has also been reported. This study evaluates the effects of repeated social defeat (RSD) during adolescence on the reinforcing and motivational effects of cocaine in adult mice and the changes induced by RSD on BBB permeability. Cocaine self‐administration, conditioned place preference and quantitative analysis of claudin‐5, laminin, collagen‐IV and IgG immunoreactivity took place 3 weeks after RSD. Mice socially defeated during adolescence developed conditioned place preference and exhibited reinstated preference with a non‐effective dose of cocaine (1 mg/kg). RSD mice needed significantly more sessions than control animals for the preference induced by 25 mg/kg of cocaine to be extinguished. However, acquisition of cocaine self‐administration (0.5 mg/kg per injection) was delayed in the RSD group. Mice exposed to RSD displayed significant changes in BBB structure in adulthood, with a marked reduction in expression of the tight junction protein claudin‐5 and an increase in basal laminin degradation (reflected by a decrease in laminin and collagen‐IV expression) in the nucleus accumbens and hippocampus. The detrimental effect induced by cocaine (25 mg/kg) on collagen‐IV expression in the hippocampus was more pronounced in RSD mice. In summary, our findings suggest that stress and cocaine can increase the long‐term vulnerability of the brain to subsequent environmental insults as a consequence of a sustained disruption of the BBB. Abstract : The current study shows for the first time that mice exposed to RSD undergo significant changes in BBB structure. RSD during adolescence induces a marked reduction in expression of the tight junction protein claudin‐5 and an increase in basal laminin degradation (reflected by a decrease in laminin and collagen‐IV expression) in the NAc in adulthood. Concomitantly, there is an increase in IgG extravasation, indicating that social defeat increases BBB permeability, probably through alterations in structural proteins.